Personal Data Protection as a Part of Information Security Management. Research Results. A Case Study - Łuczak , Jacek (Studia Oeconomica Posnaniensia, 2016)
The article stresses the importance of information and the necessity for information security management. The essential role of these issues calls for a system approach; thus, key definitions and principles of information security management have been presented in detail. The paper also takes account of numerous legal requirements, as well as the most significant requirements, as they refer to each organization, relating to personal information security. The legal basis within this scope has also been presented. The article depicts research results linked with information security management within the area of personal data protection. The research was conducted on a sample of 130 micro-,medium-sized and small enterprises. The questionnaire was extended with in-depth interviews. Moreover, the present paper embraces a case study: an IT enterprise, a provider of elearning platforms for teaching English. The case study is concerned with selected elements of the quality management system and the information security system, particularly in the aspects of personal data protection.